Etude technico-économique d’un site industriel - RIGHI Maria; KOUIDRI Mohammed ALI (Université Amar Thelidji- Laghouat FACULTE: DE TECHNOLOGIE: Département Électrotechnique, 2024)
This thesis presents a comprehensive study of the economic solutions for transitioning to renewable energy, as well as the technical and statistical procedures for conducting an energy audit within the current context of energy efficiency. With the rise in energy tariffs, energy consumption has become increasingly significant in production costs, particularly in industries where electricity, rather than natural gas, accounts for a substantial portion of turnover and added value. Historically, concerns about production line efficiency have somewhat overshadowed efforts to eliminate pollutants and reduce costs in a competitive environment characterized by strong competitiveness. Analyzing energy consumption is crucial for identifying potential improvements and resulting cost savings, while also emphasizing the continuous improvement of installation availability and capacity. Management techniques also aim to improve performance by identifying productivity gains and reducing excess costs (through measurement, counting, and analysis), which are key elements in an energy study. Renewable energies can also be considered as viable economic solutions in this field
Energie renouvelable